Rancang Bangun Sistem Integrasi Ticketing dan Reporting Klien Berbasis Web untuk IT Support Galasus - Rosmawati Pasaribu; April Petra Malonovi Marbun; Gabriel Bernard Rafa Radjali (CV. Shofanah Media Berkah, 2026)
Galasus is a company that provides IT support services and IT infrastructure management for small to medium-sized businesses. The main problems faced include unstructured work documentation, client reporting that is still done manually, the absence of an adequate request summary, and a ticketing system that is not yet integrated and still relies on a third-party application. These conditions reduce work efficiency and make it difficult to monitor work comprehensively. This study aims to design and develop a Web-Based Client Ticketing and Reporting Integration System using an iterative software development method, with observation, interviews, and literature study as data collection techniques. The system design is illustrated through a use case diagram, activity diagram, entity relationship diagram (ERD), and sequence diagram, while the implementation includes a Super Admin dashboard, client and asset management, a service desk, financial management, and an identity and access management (IAM) module. Testing was carried out using black-box testing on ten functional scenarios, all of which ran according to specification. The results show that the developed system is able to integrate the ticketing and client reporting processes into a single centralized platform, thereby improving operational efficiency, simplifying documentation, and supporting more structured, real-time work monitoring within Galasus's IT support service.